L'intégration animale et végétale comme facteur favorisant les performances des systèmes polyculture élevageTT - Mixed farming systems assessment according to crop livestock integration: case studies in Guadeloupe - Franchone, Audrey (Institut national de la recherche agronomique (France). Centre de recherches, 2016)
In the new context of the agro-ecological transition, current agricultural systems will have to produce more and better in a more constrained world. Mixed farming systems (MCLS) represent healthy alternatives to progressively achieve these objectives through crop-livestock integration (CLI). The CLI exploits synergies between cropping and livestock systems through organic fertilization with manure or plant association, the use of crop residues to feed livestock. It offers many opportunities to improve productivity, increase resource efficiency and improve the resilience of the entire agricultural system. Our objective was therefore to assess ITC at the farm level in a range of MCLS and to explain farm performance by analyzing the combination of activities and the level of integration.